Demographics and topics impact on the co-spread of COVID-19 misinformation and fact-checks on Twitter. Issue 6 (November 2021) - Burel, Grégoire; Farrell, Tracie; Alani, Harith
Abstract: Correcting misconceptions and false beliefs are important for injecting reliable information about COVID-19 into public discourse, but what impact does this have on the continued proliferation of misinforming claims? Fact-checking organisations produce content with the aim of reducing misinformation spread, but our knowledge of its impact on misinformation for particular topics and demographics is limited. In this article, we explore the relation between misinformation and fact-checking spread during the COVID-19 pandemic for different topics, user demographics and attributes. We specifically follow misinformation and fact-checks emerging from December 2019 until the 4th of January 2021 on Twitter. Using a combination of spread variance analysis, impulse response modelling and causal analysis, we highlight the bidirectional, weak causation spread behaviour between misinformation and fact-checks. Although we observe that fact-checks about COVID-19 are appearing fairly quickly after misinformation is circulated, its ability to reduce overall misinformation spread appears to be limited. This is especially visible for misinformation about conspiracy theories and the causes of the virus. Highlights: The relation between misinformation and fact-checking during COVID-19 is studied. A bidirectional weak causation between misinformation and fact-checks is observed. Fact-checks about COVID-19 appear quickly after misinformation is circulated. The ability of fact-checks to reduce misinformation spread is limited. Topics like conspiracy theories and virus causes are resistant to fact-checks.